Changes of platelet count throughout pregnancy in women with antiphospholipid syndrome. (November 2019) - Mayer-Pickel, Karoline; Stern, Christina; Eberhard, Katharina; Lang, Uwe; Cervar-Zivkovic, Mila
Highlights: Platelet count was significantly lower in women with APS to women who developed preeclampsia and to healthy pregnant women. Platelet count has a high predictive value until 28 weeks of gestation for the development of preeclampsia. Platelet count was associated with triple-positivity of antiphospholipid antibodies. In case of absence of specific lab analyses, platelet count might serve as a first risk marker for preeclampsia. Abstract: Objective: Antiphospholipid antibodies (aPL) activate several cell types, such as endothelial cells, monocytes, neutrophils, fibroblasts, trophoblasts and platelets, thus leading to thrombosis and obstetric complications in patients with antiphospholipid syndrome (APS). The aim of the present study was the longitudinal investigation of platelet count in women with APS. Additionally, platelet count in women with APS who developed preeclampsia during pregnancy were compared to women with APS and uncomplicated pregnancy for potential early detection of preeclampsia. Material and Methods: This longitudinal study included 65 women with APS, 38 women with preeclampsia and 84 women with normal pregnancies, where platelet count was determined every four weeks, starting in early pregnancy. Results: Platelet count was significantly lower in women with APS compared to women who developed preeclampsia and normal pregnancies starting at 12 weeks of gestation. The areas under the curve (AUC) for platelet count were 0.765 at 12 weeks of gestation (95% of CI of 0.634-0.896), 0.747 at 20 weeks (95% of CI of 0.600-0.894), 0.719 at 24 weeks (95% of CI of 0.555-0.882), respectively. The cut off points for platelets were 216 at 12-14 weeks of gestation, 226.5 at 20 weeks of gestation, and 163.5 at 24 weeks of gestation, respectively. Discussion: We demonstrated a significant lower platelet count in women with APS throughout gestation. Additionally, platelet count is significantly decreased in women with APS who developed preeclampsia. According to our results, platelet count seems to have a predictive value for the development of preeclampsia in these women.